A sliding-mode based controller for trajectory tracking of perturbed Unicycle Mobile Robots. (September 2020) - Mera, Manuel; Ríos, Héctor; Martínez, Edgar A.
Abstract: In this work a tracking robust algorithm for the perturbed kinematic model of an Unicycle Mobile Robot (UMR) is proposed. The control design is based on the well-known first order sliding mode control approach, with a modification that helps to reduce the chattering effect. This strategy takes into account perturbations and consider any admissible (with respect to the nonholonomic constraints) smooth reference trajectory, ensuring the convergence of the tracking error dynamics to the origin asymptotically. The resulting control input is a discontinuous switched function. Its implementability is validated through experiments using a QBot2 and compared with standard well-established control design methods for this problem.